CPRGS assessment of pilot integration of the comprehensive poverty reduction and growth strategy (CPRGS) into local socio-economic development plans ([Ha Noi], 2006)
The report "Assessment of pilot integration of the CPRGS into local socio-economic development plans" provides detail analysis on imlementation of the strategy into selected provincial socio-economic development plans ; overall assessment in terms of achievements and challenges in the inplementation process. In particular, it shows high appreciation to the effectiveness and impact of projects funded by international donors and organizations during implementing the strategy.